Molise: una strategia digitale per la divulgazione del patrimonio culturale della regione - Montereale, Lia; Ventura, Leandro (Archeomatica, 2020)
This document is divided into four sections. The first section, the introduction, analyses the transformations that the cultural sector has been undergoing in recent years driven by the development of digital tools and accelerated by Covid-19. The second section describes the cultural heritage of Molise in terms of both its tangible and intangible components. The third section shows the digital strategy developed by the Regional Secretariat for Molise in order to spread the knowledge of the cultural heritage of Molise. Included is the description of the new website www.molise.beniculturali.it, of the nine interactive maps, of the digital comic book Once upon a time in Molise, of the video Molise Land of Wonders, and of a series of online books. The fourth section is dedicated to the conclusions which stress the way in which the projects discussed have contributed to the spread of Molise's cultural heritage and opened the way to further future transformations).